G protein-coupled receptors and obesity - Pocai, Alessandro (Frontiers in Endocrinology, 2023)
G protein-coupled receptors (GPCRs) have emerged as important drug targets for various chronic diseases, including obesity and diabetes. Obesity is a complex chronic disease that requires long term management predisposing to type 2 diabetes, heart disease, and some cancers. The therapeutic landscape for GPCR as targets of anti-obesity medications has undergone significant changes with the approval of semaglutide, the first peptide glucagon like peptide 1 receptor agonist (GLP-1RA) achieving double digit weight loss (≥10%) and cardiovascular benefits. The enhanced weight loss, with the expected beneficial effect on obesity-related complications and reduction of major adverse cardiovascular events (MACE), has propelled the commercial opportunity for the obesity market leading to new players entering the space. Significant progress has been made on approaches targeting GPCRs such as single peptides that simultaneously activate GIP and/or GCGR in addition to GLP1, oral tablet formulation of GLP-1, small molecules nonpeptidic oral GLP1R and fixed-dose combination as well as add-on therapy for patients already treated with a GLP-1 agonist.